Effectiveness Of Regional Regulation Number 19 Of 2015 Concerning Protection And Empowerment Of Traditional Markets And Arrangement Of Supermarkets In Majene - Andi Aprasing; Ika Novitasari (Indonesia Prime, 2022)
This research is a qualitative descriptive research, namely describing the theoretical process of implementing Regional Regulation No. 19 of 2015 concerning the Protection and Empowerment of Traditional Markets and the Arrangement of Supermarkets that have been effectively implemented in Majene Regency. The approach used is Statute Approach and Conceptual Approach This approach is carried out by examining all laws and regulations related to the problem (legal issue) at hand, and combining views and doctrines that develop in the legal science. The results of the study, after seeing the enforcement process of Perda No. 19 of 2015, the government is not serious in the process of implementations of Perda, this is evidenced that there are still many modern markets that do not follow the rules of the regional regulations, it can be seen from the process of opening and closing modern markets that are open up to 24 hours which jeals contrary to the Perda. And there is no process of silencing the swordsmen in the people's market and the traditional market.